Prevalence of coronary artery disease in simultaneous pancreas-kidney transplantation candidates - Coelho, Juliano Cé; Siqueira, Rodrigo Morais de; Farret, Túlio Cícero Franco; Fritsch, Mariane; Fedrizzi, Renata; Goldbaum Jr, Maurício; Kroth, Leonardo V.; Hartmann, Marcelo; Falavigna, Manlio; Traessel, Moacir Alexandre; d’Avila, Domingos; Gullo Neto, Salvador; et al. (Brazilian Journal of Transplantation, 2007)
Purpose: The purpose of the study was to assess the prevalence and degree of coronary artery disease (CAD) in asymptomatic simultaneous pancreas-kidney (SPK) transplantation candidates in a Southern Brazilian transplant center. Methods: This retrospective study included 40 SPK transplantation candidates, enrolled on the transplant waiting list between May 2002 and May 2007, with type 1 Diabetes Mellitus (DM1) and Chronic Renal Failure (CRF). They were divided in two groups according to the coronary angiography: group I, patients with CAD, and group II, patients without CAD. The severity of the coronary illness was also assessed. Results: 52.5% were men and the mean age was 35.7± 9.01 years-old. The prevalence of coronary artery disease in simultaneous pancreas-kidney transplantation candidates was 40%, and 81.25% of them presented severe injury. Conclusions: Asymptomatic patients enrolled in the transplant waiting list for SPK presented a high prevalence of CAD. No independent risk factors for the CAD development have been found in the present analysis.